(untitled) (Revista Contexto & Educação, 2022)
The main objective of this study is to investigate how school knowledge is being discussed in the main education magazines in Brazil. We defend the argument that school knowledge plays a central role in curriculum theories. To this end, we used the meta-research indications and analyzed 33 articles published in A1 journals (qualis / Capes) from 2013 to 2018. It was possible to notice that the authors are affiliated with different epistemologies and address different topics in relation to school knowledge. However, little was concerned with verifying how school knowledge is being experienced in everyday school life.